2008
DOI: 10.1021/pr800423x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Human Lung Tissue Identifies Surfactant Protein A as a Marker of Chronic Obstructive Pulmonary Disease

Abstract: Chronic Obstructive Pulmonary Disease (COPD), a lung disease related to smoking, is one of the leading causes of chronic morbidity and mortality around the world. One goal in COPD research is the identification of biomarkers for early diagnosis of the disease. Here, we sought COPD-specific changes in the proteome from human lung tissue. This revealed increased levels of surfactant protein A (SP-A) in COPD but not in the normal or fibrotic lung. The results were confirmed by immunohistochemistry, morphometry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 47 publications
2
74
0
1
Order By: Relevance
“…Detailed cell profiles were assessed for all sputum samples. Since SP-A is expressed in alveolar epithelium and bronchial epithelial cells of smokers [26], and in the tracheal epithelial cells [35], all samples, i.e. also those containing epithelial cells, were included in the analyses.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed cell profiles were assessed for all sputum samples. Since SP-A is expressed in alveolar epithelium and bronchial epithelial cells of smokers [26], and in the tracheal epithelial cells [35], all samples, i.e. also those containing epithelial cells, were included in the analyses.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Induced sputum is virtually a noninvasive, safe and rather reproducible sampling technique, which is in widespread use in studies on chronic airway diseases [23][24][25], but there is very little data on SP-A levels in induced sputum. Our recent non-hypothesis driven proteomic studies on lung tissues revealed a remarkable elevation of SP-A in the lung tissues of COPD patients, even in the earlier stages of the disease [26]. Based on these observations together with the results from the large study of KOBAYASHI et al [9], it was hypothesised that plasma and sputum (a sample that derives directly from the lung), SP-A may be considered as an early marker for lung stress reaction/minimal lung injury in smokers, even before any decline of lung function has occurred.…”
mentioning
confidence: 91%
“…Two of the biomarkers studied here are previously well-characterised neutrophil-derived inflammatory molecules, myeloperoxidase (MPO) and neutrophil gelatinase-associated lipocalin (NGAL), both of which are associated with inflammation and early airway injury in smokingrelated diseases [8]. Recently using two-dimensional electrophoresis and mass spectrometry we have shown that surfactant protein A (SP-A), which has multiple immunomodulatory roles in lung host defence, is associated with cigarette smoke-induced lung injury and in the development of COPD [9][10][11]. The receptor for advanced glycation end-products (RAGE) is a multi-ligand receptor abundantly expressed in type I pneumocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics is a nonbiased screening technique that has been used to investigate various sample types including bronchoalveolar lavage fluid (BALF) (21,28,36), induced sputum (10,14,23,24), and lung tissue (17,26) to identify novel markers for COPD. In recent proteomic studies from our laboratory the major findings included an elevation of surfactant protein-A (SP-A) and a decrease of specific variants of the receptor for advanced glycation end products (RAGE) in lung tissue (25,26) and polymeric immunoglobulin receptor in sputum samples from patients with COPD (24).…”
mentioning
confidence: 99%
“…In recent proteomic studies from our laboratory the major findings included an elevation of surfactant protein-A (SP-A) and a decrease of specific variants of the receptor for advanced glycation end products (RAGE) in lung tissue (25,26) and polymeric immunoglobulin receptor in sputum samples from patients with COPD (24). Of these, SP-A and soluble RAGE have been validated in longitudinal approaches in larger cohorts (16,20).…”
mentioning
confidence: 99%